Social networks and ornithology studies: an innovative method for rapidly accessing data on conspicuous bird species - Cavalli, Matilde (2014)
We developed an innovative method for finding individuals of a conspicuous species in complex urban habitats. The aim of this study was to detect as many burrowing owl nests as possible in order to develop an ecological and behavioral study. We performed an online survey through the social network, Facebook. The results of this survey allowed us to detect and locate 36 new burrowing owl nests. We conclude that developing online surveys through social networks is an innovative and cost-effective method to obtain information about bird locations, and can complement traditional methods such as field surveys.